2017
DOI: 10.1136/bmjopen-2016-013682
|View full text |Cite
|
Sign up to set email alerts
|

Interactive web-based pulmonary rehabilitation programme: a randomised controlled feasibility trial

Abstract: ObjectivesThe aim of this study was to determine if an interactive web-based pulmonary rehabilitation (PR) programme is a feasible alternative to conventional PR.DesignRandomised controlled feasibility trial.SettingParticipants with a diagnosis of chronic obstructive pulmonary disease were recruited from PR assessments, primary care and community rehabilitation programmes. Patients randomised to conventional rehabilitation started the programme according to the standard care at their referred site on the next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
175
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(179 citation statements)
references
References 38 publications
1
175
2
1
Order By: Relevance
“…12 To date, two randomised controlled trials (RCTs) have explored the effect of unsupervised web-based or video-demonstrated individual exercise and education compared with conventional group-based PR in patients with stable moderateto-severe COPD. 13 14 The studies did not find differences between interventions for outcomes of walking capacity and respiratory symptoms. 13 14…”
Section: Introductionmentioning
confidence: 91%
“…12 To date, two randomised controlled trials (RCTs) have explored the effect of unsupervised web-based or video-demonstrated individual exercise and education compared with conventional group-based PR in patients with stable moderateto-severe COPD. 13 14 The studies did not find differences between interventions for outcomes of walking capacity and respiratory symptoms. 13 14…”
Section: Introductionmentioning
confidence: 91%
“…Smaller feasibility trials have been conducted to better understand the acceptability and uptake of digital‐based solutions. To date, they have not been of adequate sample size to conclude they are non‐inferior; however, there have been some encouraging results . These web‐based programmes have been delivered remotely, but may have included facilities allowing individuals to contact healthcare professionals remotely for personal advice.…”
Section: Pulmonary Rehabilitation In Copdmentioning
confidence: 99%
“…All these interventions, particularly if they show effects, may have a place in the care of patients with chronic respiratory conditions, but it is not helpful to move the field forward if they are branded as ‘rehabilitation’ or proposed as alternatives for pulmonary rehabilitation . In the past few years, internet‐based self‐management programmes, home‐based minimally supervised rehabilitation, tai chi exercises and yoga have all been proposed as alternatives for pulmonary rehabilitation. While these interventions may have a place in the management of some patients with chronic respiratory diseases, or may be the only alternatives in specific regions, it should be clear that these interventions are no substitute for pulmonary rehabilitation.…”
Section: The Future Of Pulmonary Rehabilitationmentioning
confidence: 99%